An experience of art therapy for patients suffering from obesity - Anzules, C; Haenni, C; Golay, A (International Diabetes Nursing, 2007)
Abstract Art therapy uses creativity in the therapeutic process itself. It is integrated within a multidisciplinary therapeutic approach to patient education, alongside cognitive-behavioural psychotherapies, medical treatment, dietetics and physical activity. The working hypothesis is that by awakening the body and mobilising all the senses, obese patients can grow more aware of their own resources and express their experiences in different ways. This can encourage more positive self-esteem. A total of 14 obese patients suffering from eating disorders took part in an art therapy programme that took place over a six-week period and consisted of six weekly sessions, each lasting two hours. Each session was broken down into three phases: phase one helps the patient to become aware of his/her body; phase two brings this awareness to creative artwork; phase three is a discussion about the pictorial art creation. The results of Coopersmith’s self-esteem inventory test showed moderate and clinically significant improvements in those who underwent the programme. During semi-structured interviews carried out two months after the workshops, patients expressed their experiences and through their words, we were able to determine what they had gained from participation. Participating in an art therapy workshop gives patients access to their own inner resources, promotes self-awareness and improves self-esteem.